2021
DOI: 10.1007/s13280-021-01534-w
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic benefits of conserving Iran’s water resources through modifying agricultural practices and water management strategies

Abstract: Sustainable development requires modifying the current consumption pattern of natural resources. This study investigates efficient tactics for reducing the unsustainability and inefficiency of human’s food-related blue water consumption alongside improving national environmental and socioeconomic status. As a case study for Iran, 15 alternative management scenarios (AMS) were defined compared to the current on-farm management, and their effects were assessed on a monthly scale. Based on the results, 45.5 billi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…To determine the variables' contribution, the co-variation of MAE with PET, P, and P+GW is calculated for the three global datasets (Figure 9). As mentioned before, GW is an important water source in semi-arid/arid regions such as in Iran and it cannot be assumed as zero due to relevant water withdrawals during recent decades [6,62,63]. The MAE, and RMSE of ET ERA5 has an inverse correlation with PET and a positive correlation with P and P+GW (Figure 9a-c, Figure S1a-c).…”
Section: Comparison Of Et Era5 Et Gleam and Et Gldas With Et Wb In ...mentioning
confidence: 89%
“…To determine the variables' contribution, the co-variation of MAE with PET, P, and P+GW is calculated for the three global datasets (Figure 9). As mentioned before, GW is an important water source in semi-arid/arid regions such as in Iran and it cannot be assumed as zero due to relevant water withdrawals during recent decades [6,62,63]. The MAE, and RMSE of ET ERA5 has an inverse correlation with PET and a positive correlation with P and P+GW (Figure 9a-c, Figure S1a-c).…”
Section: Comparison Of Et Era5 Et Gleam and Et Gldas With Et Wb In ...mentioning
confidence: 89%
“…Regions with advanced agricultural practices, better infrastructure, and technology adoption tend to achieve higher productivity. Areas with lower yields might lack access to modern farming techniques or face limitations in implementing efficient agricultural methods [57] (Figures 13 and 14). Our study reveals that maize cultivation in Iran is influenced by factors like climate, soil, water, and farming practices, varying across regions.…”
Section: Discussionmentioning
confidence: 99%
“…Upon inferring that the freshness of the plants is insu cient, the farmer starts irrigation, so de cit irrigation is not considered. De cit irrigation is assumed to be an effective strategy for environmental conservation behavior (Montazar, 2021;UT et al, 2020), and can increase water productivity as well as farmers' pro t (Du et al, 2015;Fereres & Soriano, 2007;Karandish, 2021). While the extent of technical de cit irrigation can be assessed to nd out possible options for water conservation, it can be concluded that farmers do not incorporate de cit irrigation into their decision making process.…”
Section: Irrigation Decision Criteriamentioning
confidence: 99%